A techno-economic feasibility study on the use of distributed concentrating solar power generation in Johannesburg - Bode, Christiaan Cesar (My University, 2010)
This study provides an evaluation of Concentrating Solar Power (CSP) technologies and investigates the feasibility of distributed power generation in urban areas of Johannesburg. The University of the Witwatersrand (Wits) is used as a case study with energy security and climate change mitigation being the main motivators. The objective of the study was to investigate the potential of CSP integration in urban areas, specifically investigating Johannesburg’s solar resource. This is done by assessing the performance and financial characteristics of a variety of technologies in order to identify certain systems that may have the potential for deployment. To aid the comparison of the technologies, CSP performance and cost data which were taken from multiple sources, were adjusted giving it local, present day assumptions. A technology screening process resulted in the conception of twelve alternative design configurations, each with a reference capacity of 120 kW(e). Hourly energy modelling was undertaken for Wits University’s West Campus for each of the twelve alternatives. Three configurations were further investigated and are listed below; each with a design capacity of 480 kW(e). 1. Compound Linear Fresnel Receiver (CLFR) field with an Organic Rankine Cycle (ORC). 2. Compound Linear Fresnel Receiver field with an Organic Rankine Cycle that integrates storage for timed dispatch. 3. Compound Linear Fresnel Receiver field with an Organic Rankine Cycle that integrates hybridisation with natural gas. Levelised electricity costs (LEC) of the systems were used as the basis for financial comparison. Real LECs, for the three configurations above, range between R4.31/kWh(e) (CLFR, ORC) and R3.18/kWh(e) (CLFR, ORC with hybridisation). v With the energy modelling of the hourly direct normal irradiation (DNI) input into the CSP systems, Wits University’s West Campus Electricity bill was recalculated. The addition of the solar energy input resulted in certain savings and a new LEC that is Wits-specific. These LECs ranged between R3.98/kWh(e) (CLFR, ORC) and R2.77/kWh(e) (CLFR, ORC with hybridisation). A third LEC was calculated that integrates a CSP feed-in tariff (REFIT) of R2.05/kWh. At the time of writing, a CSP REFIT of R2.10/kWh was released which favours the analysis. The analysis of the 480 kW(e) systems resulted in total plant areas of between 10350 m2 (CLFR, ORC,) and 15270 m2 (CLFR, ORC, with storage). With plant modulation, these plants can be placed on vacant land, above parking lots or on top of buildings which would also provide shading. The values obtained for the average yearly insolation was 1781 kWh/m2 based on TMY2 data. Johannesburg has a very intermittent source of DNI solar energy. The summer months in Johannesburg yield a higher peak DNI, whereas the winter months provide a more consistent average. This is due to the high amount of cloud cover experienced in summer. With this insolation, CSP electric generation is possible however, compared to the other locations, it is not ideal. Also, because of its intermittency is has been advised that certain applications such as HVAC and process heat and steam requirements be pursued. From the results, it can be concluded that power production costs through small scale CSP systems are still higher than with conventional fossil fuel options, however several options that may favour implementation were recognised. Through the analysis it was found that if the CSP generated electricity is valued at the market price ( CSP REFIT), the payback time of such systems can be decreased from 73 to 12 years (CLFR, ORC with storage). Further, due to the scale of the plants analysed, the exploitation of high efficiencies and economies-of-scale of plants with power levels above 50 MW(e), is not possible. With the introduction of these technologies vi at lower power levels, cost savings through the incorporation of other design options (such as waste heat utilisation) should be pursued. It was recognised that South Africa in general has one of the greatest solar resources in the world and should therefore be technology leaders and pioneers in CSP technology. With greater emphasis being placed on the need for renewable energy systems, it is imperative that South Africa develops its skills and a knowledge base that will work at making the implementation of renewable energy, and in particular CSP generation, a reality. Technologies identified that should be pursued for distributed generation include Linear Fresnel collectors that are easy to manufacture and don’t involve complicated receiver systems. There is also scope for developing thermal storage technologies in order to make generation more reliable.